The Impact of Artificial Intelligence on the Legal Profession - Nabila Aliya Rahmah Vansya; Meni Apriani; Joemarthine Chandra (CV. Norma Global, 2025)
The world is currently in the era of artificial intelligence, which is impacting various aspects of life, from technology and economics to health, education, and society as a whole. The power of AI is not only affecting all aspects of society but also the legal field. AI has significant legal implications for global society, and the Indonesian legal system currently lacks clear regulations on artificial intelligence, particularly in the context of its use by the legal profession in Indonesia. This can pose a risk of errors or bias in analysis, which could significantly impact the legal profession. Therefore, to anticipate the various potential threats arising from the lack of regulations regarding artificial intelligence, strict regulations are needed regarding the use of artificial intelligence related to the legal profession to ensure legal certainty. These regulations are intended to ensure that the use of AI in the legal profession is carried out responsibly and ethically based on the principles of justice, benefit, and legal certainty.